The Influence of Leadership and Innovation on Operational Performance - Galih Fajar Muttaqin (Jurnal Riset Akuntansi Terpadu, 2022)
The purpose of this study is to examine the importance of leadership and innovation in improving the operational performance of an organization. This study aims to prove that leadership and innovation can affect the company's operational performance. This research is a type of quantitative research where data is collected using questionnaires and respondents who are willing to provide information about the actual conditions that occur in the Company through answers to questionnaires that have been distributed by researchers. The research focused on 67 micro-entrepreneurs located in Serang City and District, Indonesia who are engaged in transportation, travel, education and agriculture. The analytical method used is PLS-SEM with Smart PLS analysis tool. The results of this study are leadership has a positive effect on innovation. Leadership has an effect on Operational Performance. And, Innovation has a positive effect on Operational Performance.